Nanoporous alumina templates : anodisation and mechanical characterisation - Samantilleke, A. P. (2012)
Due to applications in electronics, optoelectronics, energy storage, photocatalysis, photonics and biosensors/biomaterials, interest in onedimensional nanostructures has grown significantly during the last decade. The use of nanoporous templates as matrices for fabrication of nanostructures is now commonplace in microelectronics technology. Studies on semiconductors and dielectrics have introduced nanoporous anodised aluminium oxide as a very promising template material for the deposition of nanostructures. It is formed of an array of closely packed hexagonal oxide cells, in the centre of each of which there is a vertical hollow channel, fabricated by simple electrochemical anodisation. Anodisation, an economically viable electrochemical process, has been extensively investigated over a number of years to obtain protective and decorative films on an Al surface. The advantages in using these templates are controllability of the pore size, ratio aspect and use of low cost and simple equipment. Nanoindentation, a method that makes use of very low loads in the millinewton range has been widely used for measuring mechanical properties such as the hardness and Young’s modulus of test samples. In the first part of this chapter, the anodisation of alumina templates, as well as the electrochemical process parameters and mechanisms are discussed by means of structural and morphological characterisation. The second part is dedicated to the study of mechanical properties of nanotemplates using nanoindentation.